Evaluating HIV and STI Attitudes and Knowledge in First-Year Medical Students - Sriniwasan B Mani; Daniel O Bral; Yasamin Soltanianzadeh; Shivali Choxi; Deanna Ware; Peg Weissinger; Veronica E Michaelsen; Michael W Plankey (Journal of Student-Run Clinics, 2018)
Background: Medical students have been shown to have knowledge deficiencies and stigmatizing attitudes that may compromise their care of patients with human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs). Many medical schools now offer early exposure to patient care and encourage students to volunteer in free clinics where sexual health care is a common patient concern. In light of increased student involvement in patient care, we sought to characterize knowledge gaps and stigmatizing attitudes in first-year medical students in a major United States city.Methods: We developed a survey instrument by integrating previously validated HIV and STI knowledge questionnaires. These multiple-choice questions tested concepts such as disease transmission, clinical testing modalities, and sexual health care practice standards. In addition, we created a 4-item Likert-type scale to determine student attitudes toward patients with HIV and STIs.Results: A total of 459 medical students completed the questionnaire. The students were predominantly female (254; 55.3%), white (294; 64.1%), and Christian (241; 52.5%), with a mean age of 23.7 (standard deviation 2.45) years. The survey instrument demonstrated significant knowledge gaps in certain areas of HIV/STI testing and counseling, as well as a consistent minority of students who expressed discomfort examining or treating patients with HIV. Overall, 57.8% of the knowledge questions were answered correctly, and 14.3% of students (n=65) were not comfortable touching a patient with HIV.Conclusions: These findings suggest that medical students possess knowledge gaps and stigmatizing attitudes, which could potentially impact patient care in the practice settings in which medical students provide sexual health care. Future research should focus on 3 approaches to overcoming deficiencies in knowledge and attitudes: (1) cultural sensitivity training, (2) targeted education modules, and (3) practical testing training.